The Contexts of Political Participation: the Communication Mediation Model Under Varying Structural Conditions of the Public Sphere. (October 2022) - Borah, Porismita; Barnidge, Matthew; Rojas, Hernando
The communication mediation model asserts that the effects of news use on political participation are mostly indirect, mediated through discussion. Recent research has shown that this mediation process is stronger in countries where freedom of the press and expression are also greater. Relying on data collected during election cycles in seventeen countries between 2013 and 2018, we examine how additional country-level factors, including political freedom and digital infrastructure, moderate the indirect relationship between news use and political participation via political talk. Results provide evidence that these factors condition both outcomes, but in different ways. For protest, two of three country-level indices moderate individual-level variation in the pathway between political talk and protest. For voting, two of three country-level indices moderate aggregate-level variation in the pathway between news use and political talk. Results are discussed in light of their implications for the communication mediation model and comparative political communication research.